Ten new insights in climate science 2024 - Schaeffer, Roberto; Schipper, E. Lisa F.; Ospina, Daniel; Mirazo, Paula; Alencar, Ane; Anvari, Mehrnaz; Artaxo, Paulo; Biresselioglu, Mehmet Efe; Blome, Tanja; Boeckmann, Melanie; Brink, Ebba; Broadgate, Wendy; et al. (Elsevier, 2025)
The years 2023 and 2024 were characterized by unprecedented warming across the globe, underscoring the urgency of climate action. Robust science advice for decision makers on subjects as complex as climate change requires deep cross- and interdisciplinary understanding. However, navigating the ever-expanding and diverse peer-reviewed literature on climate change is enormously challenging for individual researchers. We elicited expert input through an online questionnaire (188 respondents from 45 countries) and prioritized 10 key advances in climate-change research with high policy relevance. The insights span a wide range of areas, from changes in methane and aerosol emissions to the factors shaping citizens’ acceptance of climate policies. This synthesis and communications effort forms the basis for a science-policy report distributed to party delegations ahead of the 29th session of the Conference of the Parties (COP29) to inform their positions and arguments on critical issues, including heat-adaptation planning, comprehensive mitigation strategies, and strengthened governance in energy-transition minerals value chains.